Culturable and unculturable potential heterotrophic microbiological threats to the oldest pyramids of the Memphis necropolis, Egypt - Rizk, Samah Mohamed; Magdy, Mahmoud; De Leo, Filomena; Werner, Olaf; Rashed, Mohamed Abdel-Salam; Ros, Rosa M.; Urzì, Clara (Frontiers in Microbiology, 2023)
A large percentage of the world's tangible cultural heritage is made from stone; thus, it deteriorates due to physical, chemical, and/or biological factors. The current study explored the microbial community inhabiting two prehistoric sites with high cultural value in the Memphis necropolis of Egypt (Djoser and Lahun Pyramids) using amplicon-based metabarcoding and culture-dependent isolation methods. Samples were examined by epifluorescent microscopy for biological signs before environmental DNA extraction and in vitro cultivation. The metabarcoding analysis identified 644 bacterial species (452 genera) using the 16S rRNA and 204 fungal species (146 genera) using ITS. In comparison with the isolation approach, an additional 28 bacterial species (13 genera) and 34 fungal species (20 genera) were identified. A total of 19 bacterial and 16 fungal species were exclusively culture-dependent, while 92 bacterial and 122 fungal species were culture-independent. The most abundant stone-inhabiting bacteria in the current study were Blastococcus aggregatus, B. saxobsidens, and Blastococcus sp., among others. The most abundant rock-inhabiting fungi were Knufia karalitana and Pseudotaeniolina globosa, besides abundant unknown Sporormiaceae species. Based on previous reports, microorganisms associated with biodeterioration were detected on color-altered sites at both pyramids. These microorganisms are potentially dangerous as physical and chemical deterioration factors and require proper conservation plans from a microbiological perspective.